The interconnectedness between Ubuntu principles and generative artificial intelligence in distance higher education institutions - Zuleika Suliman; Ntshimane Elphas Mohale; Kgabo Bridget Maphoto; Kershnee Sevnarayan (Springer, 2024)
Abstract The interconnectedness of African philosophical principles of Ubuntu with generative artificial intelligence may provide an inclusive approach to distance higher education. This fusion may improve and provide customised learning, access quality education, collaboration, inclusivity, strengthens lecturer support and development, and a culturally relevant experience that acknowledges the communal interests of all stakeholders. Generative artificial intelligence promotes epistemological access for all students irrespective of their diverse social, financial, and linguistic backgrounds and redefines higher education experiences and practices while the principles of Ubuntu prioritise the well-being of stakeholders. The objective of this conceptual article was to explore the interconnectedness between Ubuntu principles and generative artificial intelligence perspectives in distance higher education institutions to reimagine methods of teaching and learning. This article is grounded in the theory of the Ubuntu principles and advocates for a paradigm shift in higher education practices. It contends that integrating African philosophical principles into the implementation of generative artificial intelligence's learning provides a more inclusive and culturally relevant approach to education. The notable highlights confirm that Ubuntu principles dismantle oppressive systems, restore self-determination for all students and promote change and reconciliation through the use of generative artificial intelligence. This approach can be applied to distance higher education institutions to create inclusive learning experiences that gives precedence to a sense of belonging, mutual support, and ethical considerations.